Analysis and Development of Li Cultural Identity in the Learning Center - Li, Guoming; Kaewbucha, Manus; Daoduean, Chomchan (Journal of Cultural Analysis and Social Change, 2025)
This study aims to (1) explore the cultural identity of the Li people through symbolic representation, (2) design a cultural learning center that reflects Li cultural values, and (3) evaluate the effectiveness of the center in terms of visitor satisfaction and cultural transmission. An experimental research design was employed, involving in-depth interviews and satisfaction questionnaires. The sample consisted of Li culture scholars, product designers, entrepreneurs, and 400 Li culture enthusiasts. Interview data were analyzed to extract cultural symbols and interpret their identity meanings, which were subsequently integrated into the design of the cultural learning center. Six core symbols of Li culture were identified: bamboo tube rice, dragon quilt, boboat house, Li brocade, long gown buckle, and tattoo. These symbols reflect the deep-rooted historical and geographical wisdom of the Li people. The learning center was designed with the guiding principles of sustainability, immersion, and participation, balancing visitor engagement, cultural authenticity, and value. Evaluation scores indicated high levels of satisfaction: overall satisfaction with the learning center (M = 4.12), cultural center design (M = 3.80), activity design and learning process (M = 4.20), cultural product design (M = 3.83), and perceived cultural value of the center (M = 4.40). The incorporation of cultural symbols into the design of the learning center successfully preserved and communicated the Li cultural identity. Visitors responded positively to both the immersive design and the meaningful cultural content. This study offers a replicable model for integrating intangible cultural heritage into educational and experiential spaces, enhancing cultural sustainability and public engagement with ethnic minority cultures.